Integrating Religion and Science: A Desecularistic-Implementative Curriculum Model in Indonesian Islamic Universities: Study of Holistic-Integrative Approach Curriculum Development in Islamic Higher Institutions in Indonesia - Andi Murniati (Universitas Muhammadiyah Malang, 2025)
The Islamic Religious Education (PAI) curriculum at the university level in Indonesia is partial and dichotomous. Therefore, the construction of the PAI curriculum towards a desecularistic (unified) and implementable (applicable) approach is needed as a basis for providing education that is responsive to the demands of an increasingly progressive era. Educational curriculum based on a desecularistic-implementative approach is the basis for all activities, including coaching, educating, and developing the cognitive potential, character, and spirituality of students as a whole through an educational process without dichotomous barriers between religious knowledge and general knowledge (science). This research aims to analyze the construction of a PAI curriculum based on a desecularistic-implementative approach implemented at state Islamic universities (UIN) in Indonesia to solve the problematic educational dichotomy. This research uses a qualitative approach and the type of case study with participant observation and in-depth interviews as data collection techniques. Furthermore, the data was analyzed using the interactive model of Miles Huberman and Saldana. This research found that the construction of PAI curriculum was built through the